Sustainable wood polymer composites improvement based on conventional and nanotechnological approaches - Md, Rezaur Rahman. (Universiti Malaysia Sarawak, (UNIMAS), 2011)
The impovement of value-added wood products from low-quality resource through novel technology presents an excellent opportunity to maximize the value from the forest resource and thus contribtes to the global competitiveness of the wood industry in Malaysia. Conventional and nanotechnology with chemical impregnation technique becomes particularly attractive to improve some value-added properties such as mechanical properties, thermal resistance and decay resistance. The combination of nanotechnology with the traditional impregantion technique has provided a new approach to improve the wood quality attributes of vital importance to value-added applications.